LITERATUR REVIEW: APLIKASI MOLEKULER BERBASIS PCR DALAM DETEKSI DAN KARAKTERISASI Escherichia coli PADA SEKTOR LINGKUNGAN, PANGAN, DAN KLINIS - Diva Yunavita; Dwi Hilda Putri (Jurnal Biogenerasi, 2026)
Escherichia coli is a gram-negative bacterium and a key indicator of water and food contamination. Conventional PCR is a widely used molecular method for specific, rapid, and sensitive E. coli detection. This literature review systematically examines the application of conventional PCR in E. coli detection across water, food, and clinical sample matrices from 2017 to 2025. Thirteen scientific articles were reviewed regarding research objects, PCR methods, research stages, and findings. Conventional PCR using primers 16E1/16E2 (584 bp), Afa FP/RP (480 bp), and ESS (825 bp) effectively detected E. coli in diverse samples. PCR showed superior sensitivity (100%) and specificity (94.34%) compared to culture methods (Hariri, 2022). Direct PCR offered a cost-effective alternative without DNA extraction (JKG, 2025). Multiplex PCR enabled simultaneous detection of multiple virulence genes (Ekawati et al.; Microbiology Spectrum, 2024). Conventional PCR remains a reliable, specific, and rapid tool for E. coli detection across diverse sample types.